Production of Verbal Expression Sentence of Spok in Indonesian Language and Neuropsikokognitif Disorders on Patient With Broca’s Aphasia in the Medan Hospital - Gustianingsih, Gustianingsih; Effendi, Elmeida; Ali, Ali (Opción, 2019)
The objectives of this study were to classify the expression disorder of Indonesian basic sentence pattern on Patient with Broca's aphasia and to classify neurocognitive disorders in Patient with Broca's aphasia. This research uses neuropsycholinguistic theory. Theoretically this study explains the intervention and capability of memories, productions, thoughts, meanings, and emotions that are very influential in one's speech when told because of Broca's broken area in the inferior frontal gyrus. Patient of this research are 5 peoples from USU hospital. They are called as the FBA 1-5 in this research. The method of data collection is recording, interviewed and told the life story of the patient. The method of data analyzing is classifica- tin of sentence disorder and neurocognitif of the patient. This research also to see the degradation of articulatory’s patients. This study will sort out the basic sentences of expression of Indonesian language and neuropsychocog- nitive disorders by patient with Broca's aphasia. The conclusions are (1) The basic sentence patterns of Indonesian language are invalid. (2) The neuroco- nitif of FBA 1-5 as memory, mind and emotion are very uinq. FBA sufferers in this study are not able to put the basic sentence pattern of Indonesian in the context of correct and correct speech by Indonesian language.